Pemanfaatan E-Resources Dalam Temu Balik Informasi Pemustaka di UPT Perpustakaan Universitas Andalas - Alya Wenselly; Miftahul Jannah; Nilfatul Ramadani (Libraria: Jurnal Ilmu Perpustakaan dan Informasi, 2026)
This study examines the utilization of e-resources in information retrieval among users at the UPT Library of Andalas University. The research background lies in the digital transformation of academic libraries, where e-resources play a crucial role in fulfilling users' information needs. The aim is to analyze the level of utilization, the role of e-resources in information retrieval, and the challenges faced by users. This study employs a descriptive qualitative method, collecting data through observation and interviews with students from various majors. Findings reveal that while e-resources offer fast, flexible, and extensive access to academic materials, many users remain unaware or unskilled in their use due to low information literacy and insufficient training. Only one respondent reported actively using e-resources effectively, while others lacked knowledge about their existence or faced difficulty navigating database features. Challenges include limited understanding of search strategies, unfamiliarity with advanced features, and minimal outreach by the library. Despite these obstacles, e-resources hold strategic value in supporting academic productivity, distance learning, and efficient knowledge transfer. This study concludes that the effectiveness of information retrieval through e-resources can be significantly improved by enhancing digital literacy, providing regular training, and strengthening library outreach. Recommendations include designing user-oriented services and empowering librarians to serve as proactive facilitators in e-resource utilization.